2021
DOI: 10.1159/000514216
|View full text |Cite
|
Sign up to set email alerts
|

Morning Serum Cortisol Level Predicts Central Adrenal Insufficiency Diagnosed by Insulin Tolerance Test

Abstract: Introduction According to guidelines, a morning serum cortisol level <83 nmol/L is diagnostic for central adrenal insufficiency (CAI), a value >414 nmol/L excludes CAI, while values between 83 and 414 nmol/L require stimulation tests. However, there are no currently reliable data on morning serum cortisol for prediction of cortisol response to insulin tolerance test (ITT). Objective Using the receiver operating characteristic curve analysis, the purpose of this study was to detect the morning serum corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The ITT is especially preferred when damage to the hypothalamus is suspected. A number of studies have compared the ITT with alternative tests including morning cortisol [ 24 , 25 ], ACTH stimulation test [ 26 , 27 ], GHRH + arginine [ 28 ], and glucagon [ 29 ]. A recent study demonstrated that with appropriate BMI cut-off limits, the ITT is a reliable test to diagnose adult GHD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ITT is especially preferred when damage to the hypothalamus is suspected. A number of studies have compared the ITT with alternative tests including morning cortisol [ 24 , 25 ], ACTH stimulation test [ 26 , 27 ], GHRH + arginine [ 28 ], and glucagon [ 29 ]. A recent study demonstrated that with appropriate BMI cut-off limits, the ITT is a reliable test to diagnose adult GHD [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Gasco et al . [ 19 ] reported that the cut-off of morning serum cortisol concentration that best predicted a deficient response to ITT was ≤126.4 nmol/L, while the cut-off of morning serum cortisol concentration that best predicted a normal response to ITT was >444.7 nmol/L [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this study, if the cortisol evaluation is made with immunoassays using monoclonal antibodies, the grey range of 2016 guidelines potentially tighten even more allowing to identify of a narrower population to test [ 13 ]. In this context, the most recent studies stressed the importance of selecting patients to test according to the pretest probability of SAI that should be quantified by evaluating the patients’ clinical background and the morning cortisol levels [ 14 , 15 ]. Bioletto et al proposed an integrated score for the prediction of SAI when morning cortisol is in the grey zone based on morning cortisol levels, sex, and the presence of at least three other pituitary deficits, trying to narrow even more the patients that need to be tested [ 16 ].…”
Section: Patients To Be Tested and Timing For Testingmentioning
confidence: 99%